The Neurochemical Anatomy of Runway Acquisition and Extinction - Lalonde, Robert; Strazielle, Catherine (Current Psychopharmacology, 2024)
A review is presented as to the neurochemical basis of the straight runway task, usually consisting of an acquisition phase followed by an extinction phase. During the acquisition of the appetitive runway task, running speeds from the start box to the goal box progressively increase over trials and then decrease when the reward is withheld. Runway extinction is susceptible to lesions of the limbic system, including the medial frontal cortex, the hippocampus, the septum, the amygdala, and the dorsomedial thalamus. When specific neurotransmitter systems are examined, extinction was delayed when noradrenaline transmission was impeded, perhaps involving noradrenergic projections to the hippocampus and neocortex. Extinction was likewise delayed after either facilitation or blocking of dopamine transmission, a result implicating an inverted U-shaped function caused by dopamine’s role in behavioral activation or reward processes. Extinction was also delayed by indirect GABAA receptor agonists injected during acquisition, explained by drug-induced disinhibitory tendencies. This simple paradigm may provide information about the effects of a physiological manipulation on both cognition and emotion.
Keywords: anterior cingulate